MENGISI POLA GAMBAR DENGAN TEKNIK KOLASE MELALUI METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA PESERTA DIDIK DI PAUD NEGERI PEMBINA KEC. RENGAT BARAT - Endang Widia (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2016)
ABSTRACT Motor learning success can be achieved if teaching and learning takes place in a fun because that way the child's motivation will arise / rise up so that children have a strong curiosity and passion for learning. In the normal practice of collage, fine motor has not seemed to progress as they only use demonstration method in teaching. Kids less indicates a change in attitude since it tends to be passive and accept what the teacher so that the results obtained are less than the maximum. Therefore, the researcher trying to dig a way to teach learning fill pattern image with collage technique through the method of administration tasks can improve fine motor learners Group B TK Negeri Pembina Rengat District of West. In this PTK in the second cycle of activities "Fill pattern image with collage technique through the method of administration has the task can improve fine motor development of learners group B. It can be caused because the teacher has been creative in the presentation of learning.   Keyword: Collage Technique, Method of Providing Duty, Pattern Picture